A New Global Regulation on Public Health – Is the World Ready for A Second Treaty? - I Nyoman Putu Budiartha; Rahmat Mohamad (Fakultas Hukum, Universitas Warmadewa, 2022)
The World Health Organization (WHO) declared novel coronavirus (COVID-19) as a worldwide pandemic that has caused in high number of deaths in many countries and across national boundaries. In its early stage, governments all over the world have decided to implement lockdowns and closing of national border as ad hoc measures to slow down the drastic increase of the widespread of Covid-19. The United Nations through the UN General Assembly at its 74th session adopted Resolution on Global solidarity to fight COVID-19 recognized that this pandemic requires a global response based on unity, solidarity and renewed multilateral cooperation. The UN General Assembly passed under resolution on international cooperation to ensure global access to medicines, vaccines and medical equipment to face Covid-19 pandemic. This article is divided into three parts; the background of the current health security regulatory system under the International Health Regulations (IHR) 2005; the pursuance of pandemic treaty sponsored by WHO and 26 countries from Europe, Latin America and Asia and its justifications and the challenges ahead in resolving world pandemic regulatory system. The IHR aims for international collaboration